A new look at transudation: the apocrine connection - Farkaš, R; Beňo, M; Beňová-Liszeková, D; Raška, I; Raška, O (Physiological research, 2020)
Transcellular trafficking in which various molecules are transported across the interior of a cell, is commonly classified as transcytosis. However, historically this term has been used synonymously with transudation. In both cases transcellular trafficking starts with the internalization of proteins or other compounds on the basal or basolateral side of a cell and continues by their transport across the interior to the apical pole (or vice versa) where they are subsequently released. This allows a cell to release products which are synthesized elsewhere. Here, we discuss the common features of both transcytosis and transudation, and that which differentiates them. It appears that transcytosis and transudation are identical in terms of vesicular import and endosomal sorting of cargo, but completely differ in the re-secretion process. Specialized epithelial cells re-release substantial quantities of the endocytosed material, and often also a great variety. Some recent studies indicate that this is achieved by non-canonical apocrine secretion rather than by the regular vesicular mechanism of exocytosis, and takes place only on the apical pole. This massive re-release of endocytosed proteins, and potentially other compounds via the apocrine mechanism should be considered as transudation, distinct from transcytosis.
Keywords: Humans; Endocytosis; Apocrine Glands; biologický transport; zvířata; Biological Transport; exocytóza; transcytóza; Transcytosis; Animals; Exocytosis; lidé; endocytóza; apokrinní žlázy